Performance of CT scan in predicting the feasibility of primary optimal cytoreduction in ovarian cancer - Tasrin, Liza; Sultana, Jesmin; Ara, Shamim; Purabi, Ayesha Siddika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Ovarian cancer is frequently diagnosed at an advanced stage and optimal cytoreduction remains the most important prognostic factor for survival. Accurate preoperative assessment is essential to identify patients who are likely to benefit from primary debulking surgery. This study evaluated the diagnostic performance of CT scanning and a structured CT scoring system in predicting optimal cytoreduction among women with suspected ovarian cancer. This study aimed to assess the accuracy of preoperative CT findings and total CT score in determining the feasibility of optimal cytoreduction. Methods: This prospective observational study was conducted at Gynecological Oncology Unit, Department of Obstetrics and Gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh, from July 2021 to June 2022. Fifty patients with suspected ovarian cancer underwent contrast-enhanced CT scanning before primary cytoreductive surgery. Five CT parameters were evaluated and assigned scores from 0 to 2, producing a total CT score ranging from 0 to 10. CT findings were compared with peroperative findings and histopathology. Diagnostic performance, associations between CT score and surgical outcome were analyzed using SPSS. Results: Optimal cytoreduction was achieved in 70% of patients. CT showed high sensitivity for ascites, omental involvement, peritoneal thickening and lymph node metastasis. Increasing CT score correlated with a higher likelihood of suboptimal cytoreduction. A CT score ≥3 demonstrated a specificity of 100% and a significant association with suboptimal debulking. Conclusions: Preoperative CT assessment, particularly total CT score, is a valuable tool for predicting optimal cytoreduction and guiding treatment decisions in ovarian cancer.